Behavioral Health Training in Pediatric Residency Programs: A National Survey of Training Directors. Issue 4 (May 2018) - Shahidullah, Jeffrey D.; Kettlewell, Paul W.; Palejwala, Mohammed H.; Forman, Susan G.; Billups, Andrew; Anismatta, Stephanie L.; Madsen, Benjamin
ABSTRACT: Objective: To identify perceptions of behavioral health (BH) training in pediatric residency programs, the degree of involvement from behavioral health providers (BHPs), and opportunities for and barriers to innovation in training. Method: A tailored design methodology was used to target all pediatric residency program directors in the United States (N = 214). Participants were identified from the Electronic Residency Application Service website of the Association of American Medical Colleges and were asked to complete a 22-item item survey on BH training. Results: A 69.2% usable response rate (N = 148) was obtained. A total of 62.8% of directors described training in the developmental-behavioral pediatrics (DBP) rotation as optimal; 36% described BH training in the residency program as a whole (i.e., outside the DBP rotation) as optimal. Only 20.3% described "common factors" training as optimal, and the quality of training in this area was positively and significantly related to the quality of BH training in the residency program as a whole (χ 2 = 35.05, p < 0.001). The quality of common factors training was significantly higher in programs that had embedded BHPs (i.e., psychologists and social workers) in the continuity clinic than programs that did not (χ 2 = 7.65, p = 0.04). Barriers to quality training included instructional content, instructional methods, stakeholder support, and resources. Conclusion: Despite substantial improvement in residency training in BH over the last decade, additional improvement is needed. Barriers to continued improvement include training content, training methods, support from faculty and administrator stakeholders, and resource issues. Strategies derived from implementation science have the potential to address these barriers.